Dangerous Liaisons: Interactions of Cryptococcus neoformans with Host Phagocytes - Elizabeth A. Gaylord; Hau Lam Choy; Tamara L. Doering (Pathogens, 2020)
Cryptococcus neoformans is an opportunistic fungal pathogen and a leading cause of death in immunocompromised individuals. The interactions of this yeast with host phagocytes are critical to disease outcome, and C. neoformans is equipped with an array of factors to modulate these processes. Cryptococcal infection begins with the deposition of infectious particles into the lungs, where the fungal cells deploy various antiphagocytic factors to resist internalization by host cells. If the cryptococci are still engulfed, they can survive and proliferate within host cells by modulating the phagolysosome environment in which they reside. Lastly, cryptococcal cells may escape from phagocytes by host cell lysis, nonlytic exocytosis, or lateral cell-to-cell transfer. The interactions between C. neoformans and host phagocytes also influence the dissemination of this pathogen to the brain, where it may cross the blood-brain barrier and cause an often-fatal meningoencephalitis. In this review, we highlight key cryptococcal factors involved in various stages of cryptococcal-host interaction and pathogenesis.